2017
DOI: 10.1002/aenm.201700555
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Developing Metal Oxide Nanomaterials for Photoelectrochemical Water Splitting

Abstract: Photoelectrochemical (PEC) water splitting represents an environmentally friendly and sustainable method to obtain hydrogen fuel. Semiconductor materials as the central components in PEC water splitting cells have decisive influences on the device's solar‐to‐hydrogen conversion efficiency. Among semiconductors, metal oxides have received a lot of attention due to their outstanding (photo)‐electrochemical stability, low cost, favorable band edge positions and wide distribution of bandgaps. In the past decades, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
334
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(338 citation statements)
references
References 277 publications
(367 reference statements)
0
334
0
4
Order By: Relevance
“…Pan et al constructed TiO 2 p-n homojunction to realize enhanced PEC H 2 evolution performance. Virtually, it is revealed that most of the excellent PEC water splitting cocatalysts are electrocatalysts, [18][19][20] such as transition metal dichalcogenides (TMDs), [21][22][23][24][25] phosphorous metal compounds, [26][27][28] metal oxides, [29][30][31][32] metal hydroxides, [29,33] etc. [16] Alternatively, engineering cocatalysts on the surface of photoelectrodes gradually came to sight recently, as the existence of cocatalysts can bring about the reduced overpotential, accelerated reaction kinetics, enriched active sites, and suppressed corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al constructed TiO 2 p-n homojunction to realize enhanced PEC H 2 evolution performance. Virtually, it is revealed that most of the excellent PEC water splitting cocatalysts are electrocatalysts, [18][19][20] such as transition metal dichalcogenides (TMDs), [21][22][23][24][25] phosphorous metal compounds, [26][27][28] metal oxides, [29][30][31][32] metal hydroxides, [29,33] etc. [16] Alternatively, engineering cocatalysts on the surface of photoelectrodes gradually came to sight recently, as the existence of cocatalysts can bring about the reduced overpotential, accelerated reaction kinetics, enriched active sites, and suppressed corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…

While impressive solar-to-hydrogen conversion efficiency using PEC devices has been demonstrated [2,3] the development of low-cost and robust photoelectrode materials that deliver high-performance while also tolerating the harsh PEC operating conditions is still required. [4] In this regard, the semiconducting metal oxides [5] are promising photoanode materials due to their excellent durability and relative low cost. Despite the intense development of many metal oxides (e.g., Fe 2 O 3 , [6] WO 3 , [7,8] and BiVO 4

[9] ), the identification of a suitable photoanode material remains a challenge.

…”
mentioning
confidence: 99%
“…[6,7] Despite significant progress in this field, [3,[10][11][12][13][14][15][16][17] semiconductors that fulfill all these requirements rarely exist today, and the production of such semiconductors is still much sought after.Over the past few years, polymeric graphitic carbon nitride (CN) has attracted widespread attention due to its outstanding electronic properties, which have been exploited in various applications, including photo-and electrocatalysis, [18][19][20][21][22][23][24] heterogeneous catalysis, [25][26][27][28] CO 2 reduction, [29][30][31] water splitting, [32][33][34][35][36][37][38][39][40] light-emitting diodes, [41] photovoltaics, [42][43][44] and sensing. [6,7] Despite significant progress in this field, [3,[10][11][12][13][14]…”
mentioning
confidence: 99%
“…[6,7] Despite significant progress in this field, [3,[10][11][12][13][14][15][16][17] semiconductors that fulfill all these requirements rarely exist today, and the production of such semiconductors is still much sought after. [6,7] Despite significant progress in this field, [3,[10][11][12][13][14][15][16][17] semiconductors that fulfill all these requirements rarely exist today, and the production of such semiconductors is still much sought after.…”
mentioning
confidence: 99%